Immediate post-procedural functional assessment of percutaneous coronary intervention: current evidence and future directions. (5th April 2021) - Ding, Daixin; Huang, Jiayue; Westra, Jelmer; Cohen, David Joel; Chen, Yundai; Andersen, Birgitte Krogsgaard; Holm, Niels Ramsing; Xu, Bo; Tu, Shengxian; Wijns, William
Abstract: Percutaneous coronary intervention (PCI) guided by coronary physiology provides symptomatic benefit and improves patient outcomes. Nevertheless, over one-fourth of patients still experience recurrent angina or major adverse cardiac events following the index procedure. Coronary angiography, the current workhorse for evaluating PCI efficacy, has limited ability to identify suboptimal PCI results. Accumulating evidence supports the usefulness of immediate post-procedural functional assessment. This review discusses the incidence and possible mechanisms behind a suboptimal physiology immediately after PCI. Furthermore, we summarize the current evidence base supporting the usefulness of immediate post-PCI functional assessment for evaluating PCI effectiveness, guiding PCI optimization, and predicting clinical outcomes. Multiple observational studies and post hoc analyses of datasets from randomized trials demonstrated that higher post-PCI functional results are associated with better clinical outcomes as well as a reduced rate of residual angina and repeat revascularization. As such, post-PCI functional assessment is anticipated to impact patient management, secondary prevention, and resource utilization. Pre-PCI physiological guidance has been shown to improve clinical outcomes and reduce health care costs. Whether similar benefits can be achieved using post-PCI physiological assessment requires evaluation in randomized clinical outcome trials. Graphical Abstract: